2005
DOI: 10.1074/jbc.m413374200
|View full text |Cite
|
Sign up to set email alerts
|

p21-activated Kinase 1 (Pak1)-dependent Phosphorylation of Raf-1 Regulates Its Mitochondrial Localization, Phosphorylation of BAD, and Bcl-2 Association

Abstract: Raf-1 protects cells from apoptosis, independently of its signals to MEK and ERK, by translocating to the mitochondria where it binds Bcl-2 and displaces BAD. However, the answer to the question of how Raf-1 is normally lured to the mitochondria and becomes activated remains elusive. p21-activated protein kinases (Paks) are serine/ threonine protein kinases that phosphorylate Raf-1 at Ser-338 and Ser-339. Here we elucidate the molecular mechanism through which Pak1 signals to BAD through a Raf-1-activated path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
109
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(117 citation statements)
references
References 44 publications
8
109
0
Order By: Relevance
“…17,18 Both PAK1 and PAK5 interacted with Raf-1 and phosphorylated it at ser 338, which targeted it to mitochondria. 27,28 These findings imply that PAK5 may play a role in carcinogenesis. So far, PAK5 has not been correlated to any human cancers.…”
Section: Discussionmentioning
confidence: 83%
“…17,18 Both PAK1 and PAK5 interacted with Raf-1 and phosphorylated it at ser 338, which targeted it to mitochondria. 27,28 These findings imply that PAK5 may play a role in carcinogenesis. So far, PAK5 has not been correlated to any human cancers.…”
Section: Discussionmentioning
confidence: 83%
“…Several recent studies have suggested that the pro-survival effects of Raf-1 can be mediated by phosphorylating Bad on serine 112, which contributes to the inactivation and sequesterization of this pro-apoptotic Bcl-2 family member by 14-3-3 proteins (34,36). Thus, we hypothesized that inhibition of Raf-1 signaling might reduce Bad phosphorylation.…”
Section: Volume 283 • Number 4 • January 25 2008mentioning
confidence: 99%
“…Unless otherwise indicated, doses of specific inhibitors were expected to be maximally effective based on their known IC 50 values. For the Raf-1 inhibitor, we used concentrations within the values reported to block the kinase in intact cells (5-100 M) (36,37).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, both CXCL12-CXCR4 and EGF-EGFR lead to activation of the JAK-STAT signaling pathway, which regulates PIM1 expression (Soriano et al, 2003), whereas PMA treatment is also known to produce a rapid induction of PIM1 expression (Wingett et al, 1996). As some of the PIM1 target sites, like the apoptosis regulator BAD (Ser112) or the cell cycle regulator p21 (WAF1) (Thr145/Ser146), are also phosphorylated by other protein kinases, such as RAF1, PAK5, RSK2/5 for the former and PKC- or AKT for the latter (Aho et al, 2004;Jin et al, 2005;Kim et al, 2006, Oh et al, 2006Zhang et al, 2007), it is unlikely that PIM1 is the only kinase that phosphorylates CXCR4-Ser339. Although the exact mechanisms remain to be elucidated, based on our results, PIM1-regulated phosphorylation of CXCR4-S339 could provide an interaction platform for proteins that regulate receptor surface reexon December 15, 2015 jem.rupress.org…”
Section: Methodsmentioning
confidence: 99%